Pengaruh Transaksi Nontunai Melalui Quick Response Indonesian Standard (QRIS) terhadap Jumlah Tenaga Kerja UMKM - Agni Agrasevy Dwiatma; Chaikal Nuryakin (Jurnal Bina Praja, 2025)
According to data from the Central Statistics Agency for 2022, 66.48% of Indonesians have accessed the internet. This trend supports the rapid development of digitalization in payment systems, particularly with the use of Quick Response Indonesia Standard (QRIS). QRIS aims to enhance transaction efficiency, accelerate financial inclusion, and advance micro, small, and medium enterprises (MSMEs). The shift in consumer behaviour towards digital transactions due to their efficiency and speed has forced MSMEs to adapt by adopting QRIS for their payment systems. This adoption of QRIS by MSMEs will undoubtedly impact their business operations and the number of workers they need. This study uses linear regression with the Two-Stage Least Squares (2SLS) model to examine the relationship between the adoption of QRIS in cashless payment systems and the number of workers required by MSMEs. This approach is applied to address potential endogeneity arising from reverse causality, where QRIS adoption may influence labour demand, but labour capacity might also affect the decision to adopt QRIS, as well as omitted variable bias that could be correlated with both QRIS adoption and employment levels. The result indicates that QRIS has a significant positive direct effect. Although this finding does not align with the Routine-Biased Technical Change (RBTC) theory, which suggests that technology replaces routine workers, the study finds that MSMEs still need workers to serve customers and tally transaction totals (routine workers) before customers make payments through QRIS. Additionally, MSMEs are increasing their workforce by hiring family members or relatives (non-routine workers) to support their operations.